The role of new biomarkers for the diagnosis and treatment of colon cancer - Czarnecka-Czapczyńska, Magdalena; Bartusik-Aebisher, Dorota; Krupka-Olek, Magdalena; Aebisher, David; Cieślar, Grzegorz; Latos, Wojciech; Kawczyk-Krupka, Aleksandra (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Introduction. Colorectal cancer may be benign or malignant. According to the World Health Organization and CDC, it is the second most common cancer worldwide, after lung cancer. The mortality of colorectal cancer has been dropping for more than 20 years due to the improvements in screening techniques and treatments. Aim. The aim of this article is to discuss the role of new biomarkers for the diagnosis and treatment of colon cancer. Material and methods. This article is a review done in regards to discuss the role of new biomarkers for the diagnosis and treatment of colon cancer. Analysis of the literature. A review is discussed the role of new biomarkers for the diagnosis and treatment of colon cancer using current literature. Conclusion. The screening tests based on diagnostic new biomarkers may cause faster detection of cancer and risk factors, and provide prognostic information in order to adjust individual therapy.
Keywords: colon cancer; diagnosis; treatment